Enhancing Cultural Value Propagation in Lanna Artisan Patterning through Educational Intervention in Northern Thailand - Suwanreang , Chanankarn; thongsuk , Jessada; Jun-on, Nipa (Journal of Ecohumanism, 2025)
Lanna craftsmanship, renowned for its intricate patterns and deep cultural significance, faces challenges due to globalization, urbanization, and declining interest among younger generations. This research explores how intervening Lanna artisan techniques into extra-curricular activities in secondary school influences students' skill development in traditional craftsmanship, enhances their sense of cultural belonging, and fosters the creation of culturally authentic and innovative product designs. This participatory action research (PAR) involved collaboration between three local artisans as experts, 12 educators, and 25 students from four schools to develop and implement a culturally responsive intervention. The results showed changes in students' patterning skills, cultural belonging awareness, and product design outcomes. These changes developed different enhancements of students' cultural propagation, including transformation in their perceptions of cultural arts, expansion of their cultural literacy, development of their responsibility and commitment to cultural preservation, and renovation of cultural sustainability and community impact.